Deposition of TiC on γ-TiAl alloys by directly applying voltages - Chatdanai Boonruang (2018)
Two γ-TiAl alloys, Ti-47Al-2Nb-2Cr (MJ12) and Ti-47Al-2Nb-2Mn-0. 8TiB2 (MJ47), were pressed in C powder to form rods and carburized by directly applying electrical power through them at 274.3 ± 26.4 W, 80 A for MJ12 and at 293.4 ± 16.8 W, 80 A for MJ47 in Ar atmosphere. The alloys were analysed using an x-ray diffractometer (XRD), a scanning electron microscope (SEM) equipped with an energy dispersive x-ray (EDX) analyser and a Rutherford backscattering spectrometer (RBS) incorporated with NUSDAN solfware. Knoop hardness and wear resistance were improved and found to be in accord with the analytical results. © 2005 Trans Tech Publications, Switzerland.